2022
DOI: 10.1021/acsearthspacechem.2c00149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sources, Precursors, and Processing of Aerosols at a High-Altitude Tropical Site

Abstract: This work presents the results from a set of aerosol-and gas-phase measurements collected during the BIO-MAI ̈DO field campaign in Reúnion between March 8 and April 5, 2019. Several offline and online sampling devices were installed at the Mai ̈do Observatory (MO), a remote high-altitude site in the Southern Hemisphere, allowing the physical and chemical characterization of atmospheric aerosols and gases. The evaluation of short-lived gas-phase measurements allows us to conclude that air masses sampled during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 126 publications
0
8
0
Order By: Relevance
“…A clear shift in the aerosol size distribution was observed (an increase by 15% of Aitken and accumulation mode aerosols under cloudy conditions), as well as a shift in the organic aerosol chemistry with increases in MOOA, in oxalic acid concentrations and in sulfate aerosols in the PM10 offline filters. These observations together with model estimates of in-cloud processing of aerosols suggest that oxidation of gaseous precursors, and primary organic aerosol species and other aqueous phase processing have a significant impact on the sources of organic aerosol (notably oxalic acid), and on aerosol physical properties (Dominutti et al, 2022b).…”
Section: Aerosol Measurementsmentioning
confidence: 86%
See 2 more Smart Citations
“…A clear shift in the aerosol size distribution was observed (an increase by 15% of Aitken and accumulation mode aerosols under cloudy conditions), as well as a shift in the organic aerosol chemistry with increases in MOOA, in oxalic acid concentrations and in sulfate aerosols in the PM10 offline filters. These observations together with model estimates of in-cloud processing of aerosols suggest that oxidation of gaseous precursors, and primary organic aerosol species and other aqueous phase processing have a significant impact on the sources of organic aerosol (notably oxalic acid), and on aerosol physical properties (Dominutti et al, 2022b).…”
Section: Aerosol Measurementsmentioning
confidence: 86%
“…using the Time-of-Flight Aerosol chemical speciation monitor (ToF-ACSM), PM10 filter sampling using a high-volume sampler identical to those deployed at PF-1 (Dominutti et al 2022b), and by the same set of instruments deployed at DOS-2 to characterize the microphysical properties of clouds. The chemical and biological analyses of PM10 performed from filters are the same as at PF-1.…”
Section: Maïdo Observatory (Mo-5): a Receptor Site To Observe Process...mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, isoprene can be oxidized to MO-OOA during the later stages of cloud events. 20 Our knowledge of SOA production by gas-phase chemistry has been improved considerably in recent decades, while the SOA formation in clouds is less well understood. 21,22 Therefore, more field measurements are needed to understand the aqueous-phase mechanisms and important factors that critically affect the aq-SOA formation, including oxidants (e.g., hydroxyl radicals, ozone, and nitrate radicals) in cloud droplets, sunlight, droplet pH, and particle composition.…”
Section: ■ Introductionmentioning
confidence: 99%
“…suggested that the LV-OOA formation was dominated by photochemical oxidation processes during haze events in Hong Kong, while aqueous phase SOA (aq-SOA) by photooxidation contributes a large proportion to the daytime OOA in Beijing. , Mandariya et al indicated that hydroxylation is crucial for the formation of OA during fog activating periods, whereas oligomerization by addition of carbonyl (aldehyde/ketone) could occur during fog dissipating periods. Besides, isoprene can be oxidized to MO-OOA during the later stages of cloud events . Our knowledge of SOA production by gas-phase chemistry has been improved considerably in recent decades, while the SOA formation in clouds is less well understood. , Therefore, more field measurements are needed to understand the aqueous-phase mechanisms and important factors that critically affect the aq-SOA formation, including oxidants (e.g., hydroxyl radicals, ozone, and nitrate radicals) in cloud droplets, sunlight, droplet pH, and particle composition …”
Section: Introductionmentioning
confidence: 99%